2012
DOI: 10.1016/j.cell.2011.11.065
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing and Analysis of the Tasmanian Devil and Its Transmissible Cancer

Abstract: SummaryThe Tasmanian devil (Sarcophilus harrisii), the largest marsupial carnivore, is endangered due to a transmissible facial cancer spread by direct transfer of living cancer cells through biting. Here we describe the sequencing, assembly, and annotation of the Tasmanian devil genome and whole-genome sequences for two geographically distant subclones of the cancer. Genomic analysis suggests that the cancer first arose from a female Tasmanian devil and that the clone has subsequently genetically diverged dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
432
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 312 publications
(452 citation statements)
references
References 63 publications
15
432
5
Order By: Relevance
“…The thylacine sequence data was then used to assemble contigs de novo. The resulting assembly was comparable to other draft marsupial genomes [10][11][12] , with an N50 contig length of ~3.2 kilobases (Kb) and a total assembly size of ~3. 16 Gb, suggesting the thylacine genome size was similar to previously sequenced marsupials.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…The thylacine sequence data was then used to assemble contigs de novo. The resulting assembly was comparable to other draft marsupial genomes [10][11][12] , with an N50 contig length of ~3.2 kilobases (Kb) and a total assembly size of ~3. 16 Gb, suggesting the thylacine genome size was similar to previously sequenced marsupials.…”
Section: Resultsmentioning
confidence: 72%
“…Contaminating sequences were depleted by mapping to a database containing microbial and fungal genomes, leaving ~151 Gb (Supplementary Table 1). We assessed the quality of the data by mapping reads to the genome of the Tasmanian devil (Sarcophilus harrisii) 10 , the most closely related species available. Approximately 89.3% of the retained reads mapped to the complete unmasked Tasmanian devil assembly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 He reported on their recent finding that Tasmanian Devils were able to generate potent anti-tumour responses following immunisation with xenogeneic K562 cells, and that cytotoxicity generated was most likely from natural killer cells. 18 Further studies revealed that inflammatory stimuli could induce the generation of cytotoxic responses against DFTD cells.…”
Section: Australian Stories-transmissible Tumours and Hendra Virus (Hev)mentioning
confidence: 99%